2010
DOI: 10.1111/j.1601-0825.2009.01637.x
|View full text |Cite
|
Sign up to set email alerts
|

Saliva as a source of HCMV DNA in allogeneic stem cell transplantation patients

Abstract: This study shows that the real time PCR test could be useful to identify HCMV DNA in saliva and to monitor patients at risk of cytomegalovirus disease after allogeneic hematopoietic stem cell transplant. However, further studies are necessary to confirm this data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 22 publications
3
21
1
2
Order By: Relevance
“…HCMV is an important factor for morbidity and long-term outcome after allo-HSCT [35]. It has also been reported that immunosuppression related to allo-HSCT affects HCMV reactivation in the oral cavity [6,7]. In our first study [6], we did not observe any impact of HCMV presence in the saliva on recipient survival, after allo-HSCT.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…HCMV is an important factor for morbidity and long-term outcome after allo-HSCT [35]. It has also been reported that immunosuppression related to allo-HSCT affects HCMV reactivation in the oral cavity [6,7]. In our first study [6], we did not observe any impact of HCMV presence in the saliva on recipient survival, after allo-HSCT.…”
Section: Discussionmentioning
confidence: 47%
“…A previous study showed that the HCMV load in the saliva, detected by real-time PCR, had similar kinetics as compared with blood. Moreover, this study also indicated that saliva can be a useful source for real-time PCR analysis, for the monitoring and diagnosis of HCMV disease, among patients submitted to HSCT [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations